(untitled) (Physical Education, Health and Social Sciences, 2026)
Water scarcity poses a critical challenge to sustainable agriculture, particularly in arid and semi-arid regions where traditional flood irrigation systems exhibit low water-use efficiency (typically 40–60%) due to substantial losses from evaporation, deep percolation, and runoff. This review comparatively evaluates drip, sprinkler, and flood irrigation systems under water-limited conditions, focusing on application efficiency, water productivity, crop yield response, economic viability, environmental impacts, and operational challenges. Drip irrigation consistently demonstrates superior performance, achieving application efficiencies of 90–100%, global efficiencies up to 97%, and water productivity increases of 20–95% across major crops (e.g., sugarcane, tomato, and cotton, citrus). It delivers 25–50% higher yields while using 30–60% less water compared to flood methods and frequently outperforms sprinkler systems, which suffer moderate to high evaporative losses (aerial phase) under hot or windy conditions. Economic analyses reveal favorable returns for drip systems (IRR 40–65%, payback 1.5–4 years) despite higher initial investment (USD 2,500–6,000/ha), especially when combined with fertigation, which reduces nutrient leaching and N₂O emissions by up to 46%. Key limitations include emitter clogging in drip systems and energy requirements in pressurized systems. Regional evidence from severely water-stressed areas (e.g., Balochistan, Pakistan) underscores the urgency of transitioning from flood and over-exploited groundwater systems toward high-efficiency irrigation, supported by smart technologies (IoT, AI-based scheduling), solar-hybrid designs, and targeted policy interventions (volumetric pricing, subsidies, canal lining, traditional karez protection). The findings highlight drip irrigation as the most effective strategy for maximizing agronomic output, economic returns, and environmental sustainability in water-scarce environments.